Nutrition, Chronic Care, Measurement Scales and COVID-19 - Carey, Lindsay B. (Journal of religion and health, 2024)
In the year of the Olympics (Paris, 2024), this issue of JORH explores nutrition and chronic care, offers a caution regarding the use of religiosity and spiritual measurement scales, and revisits the topic of COVID-19. While the latter has been rapidly declining in terms of its global impact, each of these areas of inquiry generate a great deal of research from which humanity still has much to learn.